2019
DOI: 10.1016/j.plabm.2019.e00125
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Roche Cell-Free DNA collection Tubes to Streck Cell-Free DNA BCT s for sample stability using healthy volunteers

Abstract: Objectives To compare the Roche Cell-Free DNA Collection Tubes ® against the Streck Cell-Free DNA BCT ® s for sample stability using Cell Free DNA (cfDNA) from healthy volunteers (n = 20). Design & methods Whole blood was drawn into five Roche and five Streck tubes per volunteer, stored at room temperature and processed at five different time points (Days 0, 4, 7, 10 and 14). One volunteer had blood drawn into ×10 K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…9,14,15 Indeed, DNA extraction prior to plasma cfDNA measurement is commonplace in human studies, across multiple DNA quantification methods. 1,14,16,19 Therefore, we feel that our results with extracted-plasma cfDNA are a significant contribution to our understanding of this biomarker in horses. Our results show that median extracted-plasma cfDNA was significantly higher in emergency cases, and a subset of emergencies with colic, compared to healthy horses.…”
mentioning
confidence: 99%
“…9,14,15 Indeed, DNA extraction prior to plasma cfDNA measurement is commonplace in human studies, across multiple DNA quantification methods. 1,14,16,19 Therefore, we feel that our results with extracted-plasma cfDNA are a significant contribution to our understanding of this biomarker in horses. Our results show that median extracted-plasma cfDNA was significantly higher in emergency cases, and a subset of emergencies with colic, compared to healthy horses.…”
mentioning
confidence: 99%
“…To monitor the size distribution of the plasma DNA and therefore define the degree of contamination with high molecular cellular DNA, we analyzed the fragment size of the extracted plasma DNA using a Bio-Analyzer 2100. Circulating tumor DNA (ctDNA) has a fragment size of 90–250bp, while high-molecular cellular DNA, probably from lysed immune cells, are high molecular fragments clustering at the length of ≥1000 bp [ 21 ]. Fragment size analysis suggested that only a minor fraction of the isolated plasma DNA was in the range expected for ctDNA ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies suggested that utilization of Cell-Free DNA BCT tubes (Streck, La Vista, Nebraska) or PaxGene tubes (Qiagen, Hilden, Germany) significantly decrease contamination of the ctDNA with cellular DNA [ 13 , 20 ] by preventing cell damage due to cell-preserving reagents. However, even with the usage of such specific sample tubes, lysis of peripheral blood lymphocytes (PBLs) is not completely abolished [ 21 ]. The data presented here clearly show that our purification procedure is capable of rescuing such contaminated plasma DNA samples.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to EDTA, and considering the effectivity of cell lysis prevention, claimed utilities of the available systems were proved in several studies, including the Streck Cell-Free DNA BCT tubes [ 13 , 26 , 91 , 92 , 93 , 95 , 103 , 104 ], the CellSave Preservative tubes (CellSearch, Huntington Valley, PA, USA) [ 97 , 105 ], the Qiagen PAXgene Blood ccfDNA Tube [ 92 , 106 ], the Roche Cell-Free DNA Collection Tubes [ 12 , 98 , 107 ], the Norgen cf-DNA/cf-RNA Preservative Tubes [ 96 ] and Biomatrica LBgard Blood Tube [ 108 , 109 , 110 ]. Studies listing limitations are, however, also available.…”
Section: Sample Collectionmentioning
confidence: 99%